A systematic review of global alpha-tocopherol status as assessed by nutritional intake levels and blood serum concentrations - Péter, Szabolcs; Friedel, Angelika; Roos, Franz F.; Wyss, Adrian; Eggersdorfer, Manfred; Hoffmann, Kristina; Weber, Peter (International journal for vitamin and nutrition research, 2016)
The purpose of this study is to systematically review the published literature reporting vitamin E intake levels and serum concentrations in order to obtain a global overview of α-tocopherol status. Articles published between 2000 and 2012 were considered; 176 articles referring to 132 single studies were included. Applying an RDA (recommended daily allowance) of 15 mg/day and EAR (estimated average requirement) of 12 mg/day to all populations with a minimum age of 14 years, 82 and 61 % of mean and median data points were below the RDA and the EAR, respectively. Regarding serum concentrations, globally 13 % of the included data points were below the functional deﬁciency threshold concentration of 12 μmol/L, mostly for newborns and children. Several prospective observational studies suggest that a serum α-tocopherol concentration of ≥30 μmol/L has beneﬁcial effects on human health. Of the reported study populations and subpopulations, only 21 % reached this threshold globally. This systematic review suggests that the α-tocopherol status is inadequate in a substantial part of the studied populations.
Gesehen am 07.10.2020